1996
DOI: 10.1111/j.1365-2621.1996.17-315.x
|View full text |Cite
|
Sign up to set email alerts
|

Detoxication of rapeseed meal by Rhizopus Oligosporus sp‐T3: A first step towards rapeseed protein concentrate

Abstract: To obtain proteins from OO rapeseed meal for use in human food, a first step was realized by fermentation with Rhizopus oligosporus sp-T3. The meal's fermentation during 40 h resulted in degradation of 84% of carbohydrates, 30% of lignin and other polyphenolic components indigestible by nonruminants, and 47% of total glucosinolates which are responsible for goitre. The fermentation improves the nutritional quality of rapeseed meal by degrading undesirable factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 23 publications
7
38
0
Order By: Relevance
“…However, there were no significant differences between AA content, ash, EE and GE of CM and FCM. Enhancement of CP in FCM in the present study is in agreement with report of Rozan et al (1996) and it may explained by the loss of DM at the expense of fermentable sugars during fermentation process with LAB. The positive effects of L. salivarius in CF reduction may be attributed to the presence of polysaccharidases as studies of Skrede et al (2001Skrede et al ( , 2003 confirmed that fermentation by LAB successfully reduced levels of total and soluble dietary fibre and nonstarch carbohydrates in wheat and barley whole meals.…”
Section: Resultssupporting
confidence: 82%
“…However, there were no significant differences between AA content, ash, EE and GE of CM and FCM. Enhancement of CP in FCM in the present study is in agreement with report of Rozan et al (1996) and it may explained by the loss of DM at the expense of fermentable sugars during fermentation process with LAB. The positive effects of L. salivarius in CF reduction may be attributed to the presence of polysaccharidases as studies of Skrede et al (2001Skrede et al ( , 2003 confirmed that fermentation by LAB successfully reduced levels of total and soluble dietary fibre and nonstarch carbohydrates in wheat and barley whole meals.…”
Section: Resultssupporting
confidence: 82%
“…The CP content was significantly (P < 0.05) increased in the treated CM, but differences in EE and gross energy were not significant. The increase in CP in the present study is in agreement with the finding reported earlier by Rozan et al (1996), that the loss of dry matter at the expense of fermentable sugars during fermentation with bacteria, would result in higher percentage of CP. Later, Chiang et al (2010) also reported that CP increased slightly after fermentation, and this increase was most likely a reflection of the decline in dry matter content rather than an actual increase in protein content.…”
Section: Resultssupporting
confidence: 83%
“…It is also shown that the fermentation process lowers the concentration of crude fibre (Hu et al, 2016), as a result of decreasing the content of lignin and other indigestible polyphenolic components (Rozan et al, 1996). In our study, fermentation decreased NDF content by approximately 2 percentage points as compared with RFB, i.e.…”
Section: The Effect Of Replacing Rfb With Ffbmentioning
confidence: 52%
“…It is shown that the protein content of legumes can be increased by fermentation (Rozan et al, 1996;Hu et al, 2016). According to Mukherjee et al (2016), an increase in protein and fat contents may be partially attributed to a decrease in carbohydrate content during fermentation since microorganisms can utilise the substrate as carbon and energy sources to produce microbial protein.…”
Section: The Effect Of Replacing Rfb With Ffbmentioning
confidence: 99%
See 1 more Smart Citation